Hoplite: Building austere overlay NoCs for FPGAs - Kapre, Nachiket (2015)
Customized unidirectional, bufferless, deflection-routed torus networks can outperform classic, bidirectional, buffered mesh networks for single-flit-oriented FPGA applications by as much as 1.5× (best achievable throughputs for a 10×10 system) or 2.5× (allocating same FPGA resources to both NoCs) for uniform random traffic. We present Hoplite, an efficient, lightweight, fast FPGA overlay NoC that is designed to be small and compact by (1) eliminating input buffers, and (2) reducing the cost of switch crossbar that have traditionally limited speeds and imposed heavy resource costs in conventional FPGA overlay NoCs. We implement bufferless deflection routing cheaply, requiring the generation of only output multiplexer controls and no backpressure handshakes. Additionally, we use directional channels that help reduce crossbar cost by restricting the number of inputs to the crossbar to three instead of four. When compared to buffered mesh switches, FPGA-based deflection routers are ≈3.5× smaller (HLS-generated switch) and 2.5× faster (clock period) for 32b payloads. In a separate experiment, we hand-crafted a prototype RTL version of our switch with RLOCS that requires only 60 LUTs and 100 FFs per router and runs at 2.9 ns.